Pre-stimulus bioelectrical activity in light-adapted ERG under blue versus white background - Tsay, Katherine; Safari, Sara; Abou-Samra, Abdullah; Kremers, Jan; Tzekov, Radouil (Visual neuroscience, 2023)
To compare the baseline signal between two conditions used to generate the photopic negative response (PhNR) of the full-field electroretinogram (ERG): red flash on a blue background (RoB) and white flash on a white background (LA3). The secondary purpose is to identify how the level of pre-stimulus signal affects obtaining an unambiguous PhNR component. A retrospective chart review was conducted on four cohorts of patients undergoing routine ERG testing. In each group, LA3 was recorded the same way while RoB was generated differently using various luminances of red and blue light. The background bioelectrical activity 30 ms before the flash was extracted, and the root mean square (RMS) of the signal was calculated and compared between RoB and LA3 using Wilcoxon test. Pre-stimulus noise was significantly higher under RoB stimulation versus LA3 in all four conditions for both right and left eyes (ratio RoB/LA3 RMS 1.70 and 1.57 respectively, p < 0.033). There was also no significant difference between the RMS of either LA3 or RoB across protocols, indicating that the baseline noise across cohorts were comparable. Additionally, pre-stimulus noise was higher in signals where PhNR was not clearly identifiable as an ERG component versus signals with the presence of unambiguous PhNR component under RoB in all four groups for both eyes (p < 0.05), whereas the difference under LA3 was less pronounced. Our study suggests that LA3 produces less background bioelectrical activity, likely due to decreased facial muscle activity. As it seems that the pre-stimulus signal level affects PhNR recordability, LA3 may also produce a better-quality signal compared to RoB. Therefore, until conditions for a comparable bioelectrical activity under RoB are established, we believe that LA3 should be considered at least as a supplementary method to evaluate retinal ganglion cell function by ERG.